オーロラ タイ イメージング リオメータ デ カンソク サレタ チジキ キョウヤクテン イド ノ キセツ ヘンカ - 藤田, 裕一; フジタ, ユウイチ; 山岸, 久雄; ヤマギシ, ヒサオ; 佐藤, 夏雄; サトウ, ナツオ; Fujita, Yuiti; Yamagishi, Hisao; Sato, Natsuo (1998)
P(論文) 地磁気共役点は固定した点ではなく季節や時刻とともに変動する点だと考えられ, これを実証するため従来から共役点での光学観測によるオーロラ形状の比較が行われてきた。しかし, 光学観測では日照や天候の条件のため年間を通じた統計解析は不可能である。本研究では, 昭和基地-チョルネス共役観測点に設置されたイメージングリオメータで得られた電離層吸収データを用い, 真夜中前のオーロラブレークアップ時に発生する東西に伸びた帯状吸収領域の緯度を比較することにより, 共役点位置の季節変化を求めた。約2年間の連続したデータの統計により, 以下の特性が明らかにされた。(1) オーロラブレークアップ時の吸収領域の高緯度方向への移動速度は, 昭和においてはチョルネスより平均で約15%高い。(2) この時間帯では, アイスランド側に投影された昭和の共役点は, 6月頃チョルネスより最も低緯度側, 12月頃最も高緯度側に位置する。(3) この季節変化は, IGRF 1995とTsyganenko 1989モデルを組み合わせて用いた計算結果とよく一致する。 Seasonal variation in the latitude of geomagnetically conjugate point was obtained statistically using the imaging riometers at Syowa-Tjornes conjugate pair stations. The conjugate point was evaluated experimentally from the relative location of band-type CNA (Cosmic Noise Absorption) appearing at the conjugate stations, associated with auroral breakups in premidnight hours. The statistical analyses were made for poleward moving CNA-bands observed during February 1992 to December 1993. Following characteristics are obtained. (1) The poleward expanding speed of the CNA-bands differs significantly between the two hemispheres : it is faster at Syowa than Tjornes in Iceland by 15% on average. This difference may be attributable to an interhemispherical asymmetry of the magnetic flux tube radii mapped to the ionospheres, which is caused by the differences in the geomagnetic field strength and dip angles between the both stations. (2) The conjugate point of Syowa mapped to the northern hemisphere moves most equatorward in June and most poleward in December from Tjornes. The latitudinal range of the seasonal displacement is about 200km for the average geomagnetic activities of Kp=4. (3) The seasonal displacement agrees well with the calculations of the conjugate points using the combination of IGRF 1995 and Tsyganenko 1989 geomagnetic field models. departmental bulletin paper